2013
DOI: 10.4187/respcare.01818
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Fluid Amino-Terminal Brain Natriuretic Peptide in Patients With Pleural Effusions

Abstract: BACKGROUND: Definite diagnosis of transudative or exudative pleural fluids often presents a diagnostic dilemma. The aim of this study was to evaluate whether amino-terminal brain natriuretic peptide (NT-proBNP) levels in pleural fluid has a diagnostic value for discriminating heart-failurerelated pleural effusions from non-heart-failure effusions. METHODS: Sixty-six subjects (40 male, mean age 61 ؎ 18 y) with pleural effusions were included. Samples of pleural fluid and serum were obtained simultaneously from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…One limitation of the present study needs to be addressed. The kit for assaying NT-proBNP in this study differs from the commonly used electrochemiluminescence immunoassay for NT-proBNP offered by Roche Diagnostics; however, the diagnostic cutoff of NT-proBNP we established is well within the range reported in other studies using the Roche assay [5] , [10] , [12] , [14] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 68%
“…One limitation of the present study needs to be addressed. The kit for assaying NT-proBNP in this study differs from the commonly used electrochemiluminescence immunoassay for NT-proBNP offered by Roche Diagnostics; however, the diagnostic cutoff of NT-proBNP we established is well within the range reported in other studies using the Roche assay [5] , [10] , [12] , [14] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 68%
“…In total, 14 studies involving 599 patients with HF and 1055 patients without HF were included in the present work [ 25 38 ]. A flow chart depicting the study selection process is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of these 14 studies ranged from 28 to 398. Half of the studies were prospective [ 25 , 27 , 32 , 34 36 , 38 ], five were retrospective [ 26 , 28 – 31 ], and the remaining two did not report their design characteristics [ 33 , 37 ]. The control groups generally comprised patients with malignancy, tuberculosis, parapneumonic effusion, pulmonary embolism, hepatic hydrothorax, postcardiac injury syndrome, collagen disease, and other conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Мозговой натрийуретический пептид -нейрогормон, высвобождаемый кардиомиоцитами желудочков в ответ на повышение давления или объема. Позволяет диагностировать плевральные выпоты сердечного генеза с чувствительностью и специфичностью 94%, позволяет выявлять 80% транссудатов, пропущенных по критериям Лайта [34,36]. В связи с высоким уровнем корреляции его содержания в плазме крови и в выпоте, нет необходимости исследовать уровень мозгового натрийуретического пептида в плевральной жидкости при его повышенном уровне в крови [35].…”
Section: типичные жалобы и анамнез при плевральных выпотахunclassified